Analisis Kandungan Pewarna Sintetis Pada Jajanan Pasar Di Kota Mataram Dengan Kromatografi Kertas - Fardani, Roushandy Asri (JSN : Jurnal Sains Natural, 2023)
Food Additives are ingredients that are usually not used, not the main ingredient of food, these ingredients are intentionally added to food. One food that is often added with food additive is jam. Jam is a food made simply from sour-tasting fruits such as strawberries, grapes, blueberries and pineapple. Jam making is strongly influenced by the type of fruit used, the temperature and the jam making process (Javanmard and Endan, 2010). The types of jam bread from various brands and unbranded ones can be found in traditional markets as well as in modern markets. Synthetic dyes are generally cheaper, easier to use, stable, better coloring power, and have a wider color range (Nollet, 2004). Some synthetic dyes are so harmful to health that their use is not permitted. One example, the red color given to food is Rhodamin B (Djalil et al., 2005). The type of research used is qualitative research conducted to determine the type of coloring substances contained in branded jam bread and unbranded jam bread using the paper chromatography method. Qualitative examination with paper chromatography method and this examination to see the type of coloring substances contained in the sample. Based on the results of the qualitative analysis, it is known that of the 4 samples, 2 branded jam samples and 2 unbranded jam samples use permitted coloring agents, namely Sample A1 does not contain synthetic dyes and Sample B does not contain synthetic dyes. After qualitative examination, it was found that there was no use of coloring agents that were not permitted in the branded jam samples. In the unbranded jam after qualitative examination was not found the use of coloring substances that are not permitted. Rhodamine B is a textile dye that can trigger diarrhea, allergies, cancer or kidney damage. After the research was conducted, it was found that from the branded and unbranded jam samples, no synthetic dyes were found. Based on the results of the examination on the types and synthetic dyes of branded jam and unbranded jam circulating in Keru Narmada Market, it can be concluded as follows: The results of the examination of branded and unbranded jam found no synthetic dyes.